Fruit and Vegetable Consumption Interacts With HNF1A Variants on the C-Reactive Protein - Shin, Dayeon; Lee, Kyung Won (Frontiers in Nutrition, 2022)
Epidemiological studies have demonstrated the inverse association between fruit and vegetable intake and inflammation. However, the mechanism by which inflammation-related genes interact with fruit and vegetable intake and the role of these combinations in inflammation remain unclear. Therefore, we assessed the interactions between fruit and vegetable intake and hepatic nuclear factor 1 alpha (HNF1A) genetic variants on the C-reactive protein (CRP) levels. Baseline data from the Ansan and Ansung Cohort Study of the Korean Genome and Epidemiology Study (KoGES) were used. A total of 7634 participants (3700 men and 3984 women) were included in the analyses. Fruit and vegetable intake was assessed using semi-quantitative food frequency questionnaire data. Genotyping information for HNF1A was extracted from the Affymetrix Genome-Wide Human SNP array 5.0. Inflammation was determined after overnight fasting by measuring CRP levels using automated analyzers. Multivariable logistic regression was used to estimate the adjusted odds ratio (AOR) with a 95% confidence interval (CI). In the fully adjusted model, men and those with the GG genotype of HNF1A rs2393791 and high fruit intake had lower odds of elevated CRP levels compared to those with the AA genotype and low fruit intake (AOR 0.50, 95% CI 0.38‒0.67; AOR 0.73, 95% CI 0.55‒0.97, respectively). Men and women with the rs2393791 GG genotype and high vegetable intake had lower odds of having elevated CRP levels compared to those with the AA genotype and low fruit intake (AOR 0.57, 95% CI 0.43‒0.75; AOR 0.65, 95% CI 0.49‒0.86, respectively). Men and women with the GG genotype and high total fruit and vegetable intake had lower odds of having elevated CRP levels. These findings indicate that fruit and vegetable intake interacts with HNF1A genetic polymorphisms, consequently influencing the inflammation levels.